Worklife Balance on Employee Engagement among Women in Technical Education (Wited) in Polytechnics in Osun State, Nigeria - Oluwatobi, Omotoye (Annals of Spiru Haret University. Economic Series, 2021)
This study discussed the influence of work-life balance on employee engagement among women in technical education (WITED) in Polytechnics in Osun State. This is with the view of ensuring successful blending of world of work with personal responsibilities in optimal harmony. The study adopted a descriptive survey research design. The population of the study was made up of women in technical education in government polytechnics, in Osun State. A total of 750 workers were selected from Women in the Technical Education through simple random sampling technique. Two research instruments titled Work-life balance Scale (WLBS) and Employee engagement scale (EES) adapted and modified were used to collect data for the study. The test retest reliability of the instruments administered within two weeks interval yielded .78 and 0.80 respectively. The response format used was the Likert format with options ranging from Strongly Agree (4) Agree (3) Strongly Disagree (2) and Disagree (1). All the instruments were divided into two parts. Part A solicited responses on personal information about the respondents while part B collected data on the variables under study. Multiple Regression Analysis was used to test the hypotheses raised at 0.05 alpha level. Result established that flexible work arrangement had coefficients β = 0.190, t = 1.688, p = 0.007 < α =0.05, indicating a significant influence of flexible work arrangement on employee engagement. Finding also, showed that work-life conflict also showed a significant influence on employee engagement with the coefficients, β = 0.385 t =-1.184, p = 0.002 < α =0.05, which indicated a negative influence of work life conflict on employee engagement. Based on the findings the study concluded that work-life balance should be comfortably blended with personal engagement so as to significantly engender employee engagement among Women in Technical Education (WITED) in Polytechnics in Osun. And that adequate skill and knowledge of assigned task should be sought to balance the fits in employee engagement among Women in Technical Education (WITED) in Polytechnics in Osun. The study recommended that management should build a work environment that attracts, retains, and motivates its employees to help them work comfortably to increase organization productivity, and that organizations should embrace flexible work schedule strategies as this would positively influence employee engagement.